1993
DOI: 10.2166/wst.1993.0528
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms and Environmental Protection

Abstract: Biofilms are the result of adhesion and growth of microorganisms at interfaces. They consist mainly of water (70-95 % wet weight), held by the highly hydrated extracellular polymers (EPS, 70-95 % dry weight) in which the microorganisms are embedded. Adhering cells differ from their suspended counterparts in both activity and resistance to toxic substances. The cells are immobilized next to each other and form well organized consortia, capable of performing sequential degradation processes. Biofilms are ubiquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
4

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 0 publications
1
69
0
4
Order By: Relevance
“…It is expected that these biofilms exist on the air/liquid interface of the rainwater tank and the solid/liquid interface within the rainwater tank, pipes and in bioretention systems (Blanchard & Syzdek, 1970;Characklis & Marschall, 1990;Flemming, 1993;Hermansson & Dahlbäck, 1983;Sawyer et al, 2010;Spiers et al, 2003;Spinks et al, 2003). The velocity of flow within the rainwater tank itself is slow, even when it is raining and when the tank is utilised.…”
Section: Processes Within the Rainwater Tankmentioning
confidence: 99%
“…It is expected that these biofilms exist on the air/liquid interface of the rainwater tank and the solid/liquid interface within the rainwater tank, pipes and in bioretention systems (Blanchard & Syzdek, 1970;Characklis & Marschall, 1990;Flemming, 1993;Hermansson & Dahlbäck, 1983;Sawyer et al, 2010;Spiers et al, 2003;Spinks et al, 2003). The velocity of flow within the rainwater tank itself is slow, even when it is raining and when the tank is utilised.…”
Section: Processes Within the Rainwater Tankmentioning
confidence: 99%
“…The increase in the thickness was probably due to cross-linking between glutaraldehyde and the amine group of proteins or enzymes found on bacterial cell walls (Simons et al 2000). Moreover, glutaraldehyde may also react with protein which is the one of the predominant constituents of biofilm extracellular polymeric substances (EPS) apart from polysaccharide (Christensen and Characklis, 1990;Flemming, 1993;Norwood and Gilmour, 2000). Figure 2 shows that COD removal of the control unit (without glutaraldehyde) was 71.73 ± S.D.…”
Section: Biofilm Formationmentioning
confidence: 99%
“…Microbial biofilms play an essential role in engineered processes especially in biological treatment and energy production (Flemming, 1993;Bryers, 2000). They have been reported to have higher resistant to toxic compounds than free cell systems (Sofer et al 1990;Lazarova and Manem, 2000).…”
mentioning
confidence: 99%
“…there was more than 88% of organic material deposited in all fouling matrixes. It has been reported that membranes are likely biofouled if the fouling layers contain a large quantity of microorganisms and more than 70% of organics substances [57,137]. Hence, the LOI results, along with the ATP measurement, confirmed the presence of large amount of organic matters on the surface of membranes, suggesting these membranes (RO1-5) were covered by a mixture of organic and biological fouling.…”
Section: 3 Loss On Ignition (Loi)mentioning
confidence: 65%
“…Biofilm is mainly made up of 70-95% water. Within 5-30% of dry weight, 70-95% of EPS hold microbial cells [57]. Beside the embedded microorganisms, EPS consist 40-95% of polysaccharides, up to 60 % of proteins and small amount of nucleic acids, lipids and other biopolymers [58].…”
Section: Structure and Compositionmentioning
confidence: 99%